Nodes Deployment Scheme of Heterogeneous Wireless Sensor Network Based on Organic Small Molecule Model - Juwei Zhang; Yu Wang; Yachuang Liu; Qiangyi Li (Institute of Advanced Engineering and Science, 2015)
For nodes deployment of heterogeneous sensor network, based on different probability sensing models of heterogeneous nodes, refer to organic small molecule model, ‘class molecule’ sensing model of heterogeneous nodes is proposed. Combined with DSmT data fusion model, the changes of network coverage ratio after using the new sensing model and data fusion algorithm is studied. According to the research results, the node-deployment strategy of heterogeneous sensor networks based on organic small molecule model (NHOS) is proposed. Sensor network simulation model is established using MATLAB software, the results show the effectiveness of the algorithm, the coverage of network and detection efficiency of nodes are improved, the lifetime of network is prolonged, energy consumption and the number of deployment nodes is reduced, and the scope of perceiving is expanded. As a result, NHOS can improve the detection performance of the network.